Mobile money adoption, input use, and farm output among smallholder rice farmers in Ghana - Awal Abdul-Rahaman; Awudu Abdulai (Agribusiness, 2021)
Financial exclusion continues to be a major challenge to smallholder farmers' participation in agricultural value chains in developing countries. Digitizing procurements and other forms of transactions using mobile money technology among value chain actors is essential for ensuring financial inclusion and enhancing agricultural value chain transformation. This study examines the factors influencing the adoption of mobile money technology and the impact of the technology on production input use and farm output, utilizing data from a cross-sectional survey of smallholder rice farmers in northern Ghana. A linear regression with endogenous treatment effects method is employed to account for both observable and unobservable selection bias. The results reveal positive and significant marginal effect of mobile money technology on input use and farm output. Adopters of the technology applied 18% and 13% more fertilizer and herbicides, respectively than nonadopters. The output increased by about 4% for the adopters. The results also show that mobile money technology adoption, input use and farm output are significantly influenced by education, farmer-based organization (FBO) membership, access to credit, input prices, and location fixed effects. Expansion of mobile technology networks, increased investment in education, credit facilities, and FBOs can be quite relevant in promoting the adoption of mobile money technology in Ghana. [EconLit citations: C34, C35, Q12, Q13]
Keywords: 630; farm output; input use; mobile money technology; treatment effects model